2018
DOI: 10.1162/jocn_a_01244
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Frontal Aslant Tract in Speech Planning: A Neurosurgical Case Study

Abstract: Frontal and temporal white matter pathways play key roles in language processing, but the specific computations supported by different tracts remain a matter of study. A role in speech planning has been proposed for a recently described pathway, the frontal aslant tract (FAT), which connects the posterior inferior frontal gyrus to the pre-SMA. Here, we use longitudinal functional and structural MRI and behavioral testing to evaluate the behavioral consequences of a lesion to the left FAT that was incurred duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 76 publications
6
34
0
1
Order By: Relevance
“…Our regression analyses confirmed that the correlations between FAT microstructure and morpheme-based fluency were not explained by standard verbal fluency tests. The apparent specificity of the correlations with the morpheme-based task are in line with several case studies where surgical resection damaging the left FAT induced speech disruptions that were sensitive to grammatical constraints (Chernoff et al, 2019(Chernoff et al, , 2018Sierpowska et al, 2015). Of particular relevance is the case reported by Sierpowska and colleagues (2015), where damage to the left FAT elicited production errors characterized by inappropriate application of morphological rules.…”
Section: Morpheme-based Fluency Is Associated With Ventral and Dorsalsupporting
confidence: 77%
“…Our regression analyses confirmed that the correlations between FAT microstructure and morpheme-based fluency were not explained by standard verbal fluency tests. The apparent specificity of the correlations with the morpheme-based task are in line with several case studies where surgical resection damaging the left FAT induced speech disruptions that were sensitive to grammatical constraints (Chernoff et al, 2019(Chernoff et al, , 2018Sierpowska et al, 2015). Of particular relevance is the case reported by Sierpowska and colleagues (2015), where damage to the left FAT elicited production errors characterized by inappropriate application of morphological rules.…”
Section: Morpheme-based Fluency Is Associated With Ventral and Dorsalsupporting
confidence: 77%
“…Smoothing and regularization were performed using FSL's fugue tool (www.fmrib.ox.ac.uk/fsl), and three-dimensional (3D) Gaussian smoothing was applied using sigma = 4 mm (25). The magnitude image was warped on the basis of this smoothing, with y as the warp direction, following a previous study (26). Eddy current correction was performed using FSL's eddy_correct tool, which takes each volume of the diffusion-weighted image and registers it to the B0 image to correct for both eddy currents and motion.…”
Section: Dti Preprocessing and Analysismentioning
confidence: 99%
“…Nevertheless, functional MRI also can unambiguously estimate the exact location of speech areas. Researchers should put more effort into studying DTI in terms of speech preservation as awake craniotomy resection is still more reliable in this case [37].…”
Section: Arcuate Fasciculus (Af)mentioning
confidence: 99%
“…In clinical practice, FAT could be determined to be a means of DTI in patients for whom an awake craniotomy is planned [43]. Baker et al suggested that FAT and "crossed FAT" are of great importance for tumours infiltrating SMA and pre-SMA [37,44].…”
Section: Frontal Aslant Tractmentioning
confidence: 99%